Предмет: Математика,
автор: 8savalex
№ 2. Упростите выражения.
a) (sin a - cos a)² + sin 2a;
б) 1-4 sin² cos² a;
Ответы
Автор ответа:
1
Ответ:
a)(sins)^2-2sinacosa+(cosa)^2+2sinacosa=
=(sina)^2+(cosa)^2=1
b)(1-2sinacosa)(1+2sinacosa)=
=(sina-cosa)^2(sina+cosa)^2=
=[(sina)^2-(cosa)^^2]^2=
=(-cos2a)^2=(cos2a)^2
Пошаговое объяснение:
Похожие вопросы
Предмет: Українська мова,
автор: kiselevatatyna92
Предмет: Другие предметы,
автор: damirnurtdinov1990
Предмет: Окружающий мир,
автор: mbondareva111
Предмет: Английский язык,
автор: darigakalilova693
Предмет: Математика,
автор: LegendaryPlay